1983
DOI: 10.3354/meps012091
|View full text |Cite
|
Sign up to set email alerts
|

Changes in biomass and chemical composition of spider crab (Hyas araneus) larvae reared in the laboratory

Abstract: Larval and early post-larval growth has been investigated in Hyas araneus L. (Majidae) reared in the laboratory. Growth was measured as dry weight (DW), ash-free dry weight (AFDW), carbon (C), nitrogen (N), hydrogen (H), gross biochemical constituents (protein, lipid, carbohydrate, chitin, ash) and energy (calculated separately from carbon and biochemical composition). During larval development, i. e. from freshly hatched zoea-1 to late megalopa, all these cr~teria of b~omass increase by factors ranging betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
29
2

Year Published

1985
1985
1992
1992

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 21 publications
3
29
2
Order By: Relevance
“…Carbohydrates other than chitin play only a minor role in the biochemical composition of crabs. Protein amounted to 31-50 % of AFW (or 15-34 % of W), which is similar to values found in previous studies on larval and juvenile H. araneus (Anger et al, 1983;Anger & Hirche, 1990), and comparable with an average value of 42 % of APW (31% of W) found in a crayfish .…”
Section: Discussionsupporting
confidence: 76%
See 4 more Smart Citations
“…Carbohydrates other than chitin play only a minor role in the biochemical composition of crabs. Protein amounted to 31-50 % of AFW (or 15-34 % of W), which is similar to values found in previous studies on larval and juvenile H. araneus (Anger et al, 1983;Anger & Hirche, 1990), and comparable with an average value of 42 % of APW (31% of W) found in a crayfish .…”
Section: Discussionsupporting
confidence: 76%
“…It was in the present material higher than that observed by Anger et al (1983) and Anger (1984), but lower than the values reported by Anger & Hirche (1990), although in all these studies juvenile crabs had been reared under identical conditions. In addition to this intraspecific variation in the average absolute amounts of biomass, variation was found also in the relative proportions of single constituents, and in the patterns of absolute change.…”
Section: Discussioncontrasting
confidence: 55%
See 3 more Smart Citations